2014
DOI: 10.4161/15592294.2014.983367
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated Class I histone deacetylases are indicators of poor prognosis in multiple myeloma

Abstract: Abbreviations:Histone deacetylases (HDAC) control gene expression through their ability to acetylate proteins, thereby influencing a diverse range of cellular functions. Class I HDAC (HDAC1-3 and 8) and HDAC6 are predominantly upregulated in malignancies and their altered expression in some cancers has a significant prognostic implication. The expression and prognostic consequence of dysregulated Class I HDAC and HDAC6, key players in multiple myeloma (MM), are unknown. This study hypothesized that HDAC are dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
118
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 154 publications
(119 citation statements)
references
References 53 publications
1
118
0
Order By: Relevance
“…Isolation of bone marrow mononuclear cells (BMMNC), determination of MM cell proportion and isolation of CD138 + cells from MM cells and plasma cells from healthy donors was performed as previously described [47]. Briefly, Ficoll Plaque Plus (GE Healthcare, Chicago, IL, USA) was utilized to isolate BMMNC as per manufacturer’s guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…Isolation of bone marrow mononuclear cells (BMMNC), determination of MM cell proportion and isolation of CD138 + cells from MM cells and plasma cells from healthy donors was performed as previously described [47]. Briefly, Ficoll Plaque Plus (GE Healthcare, Chicago, IL, USA) was utilized to isolate BMMNC as per manufacturer’s guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…In general histone acetylation is associated with transcriptional activation, and recent investigations revealed that HDAC1, 2, 3 and 6 are highly expressed in MM contributing to the malignant phenotype (91). Conversely, mutations in the HAT CREBBP appear more common in relapsed MM and gene copy loss of CREBBP and EP300 is observed in 10% MM patients (Figure 1).…”
Section: Histone Acetylationmentioning
confidence: 99%
“…Higher levels of HDAC activity are associated with the silencing of differentiation and tumour suppressor genes, leading to oncogenesis [1]. Increased HDAC levels have been reported in several human tumours and cancer cell lines [2][3][4], including multiple myeloma [5]. Panobinostat (Farydak Ò ) is a nonselective HDAC inhibitor [6], a relatively new class of anticancer agents.…”
Section: Introductionmentioning
confidence: 99%